2019
DOI: 10.1242/bio.043968
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of plant growth promoting rhizobacteria and their benefits on growth and phosphate nutrition of faba bean and wheat

Abstract: In recent years, more attention has been paid to plant growth promoting (PGP) rhizobacteria use as a biofertilizer alternative to chemical fertilizers, which might cause damage to the environment. The main objective of this work was to evaluate the field application of PGP bacteria and rhizobial strains on the productivity of two food crops extensively used in Morocco; Vicia faba L. and Triticum durum L. A field experiment with four treatments was designed: (1) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 34 publications
(42 reference statements)
1
26
0
Order By: Relevance
“…Moreover, K-silicate could stimulate the availability of soil nutrients, such as N, which has a direct positive relationship with the activities of soil enzymes [ 36 , 37 ]. The direct application of PGPR to the soil or in the inoculated seeds greatly increases microbial biomass and community diversity, which influenced the soil enzymes [ 38 ]. In this regard, the dual application of K-silicate and PGPR maximized the soil health status.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, K-silicate could stimulate the availability of soil nutrients, such as N, which has a direct positive relationship with the activities of soil enzymes [ 36 , 37 ]. The direct application of PGPR to the soil or in the inoculated seeds greatly increases microbial biomass and community diversity, which influenced the soil enzymes [ 38 ]. In this regard, the dual application of K-silicate and PGPR maximized the soil health status.…”
Section: Discussionmentioning
confidence: 99%
“…As concerned to P solubilization, almost all strains were found positive. Bechtaoui et al 56 showed that the application of plants with insoluble phosphate and PGP bacterial strain improved the wheat and faba beans growth. Abou-el-Seoud and Abdel-Megeed 57 improved the wheat growth with the application of P and K solubilizing B. sp.…”
Section: Discussionmentioning
confidence: 99%
“…Each actinobacterial isolate was grown in 100 mL of National Botanical Research Institute's phosphate growth medium devoid of yeast extract (NBRIY) broth, supplemented with tricalcium phosphate (Ca 3 (PO 3 ) 2 ) as a source of inorganic phosphate [26]. The inoculum was incubated at 28 • C on a rotatory shaker at 180 rpm.…”
Section: P Solubilizationmentioning
confidence: 99%